Pilot study: The effect of eight weeks of aerobic training in the two phases of light and dark circadian rhythm on genes (OCT4, NANOG, SOX2, REX1) in bone tissue of diabetic mice - Maryam Janbozorgi; Asma Taheri; Masoumeh Hosseinzadeh; Sahar Ghafaripur (PLoS ONE, 2026)
Introduction Diabetes mellitus impairs bone metabolism through chronic hyperglycemia, oxidative stress, and inflammation, leading to reduced osteoblast activity and downregulation of key pluripotency genes such as Octamer-binding transcription factor 4 (OCT4), Nanog homeobox (NANOG), SRY-box transcription factor 2 (SOX2), and Reduced expression protein 1 (REX1).The present study investigated whether the timing of aerobic exercise (morning vs. evening) influences the expression of pluripotency genes in the bone tissue of diabetic mice. Methods Eighteen male NMRI mice were assigned to healthy control, diabetic control, or diabetic exercise groups. Diabetes was induced using a high-fat diet combined with low-dose streptozotocin. Aerobic training was performed for eight weeks at either ZT3 (morning) or ZT15 (evening), five sessions per week, at 50–60% Vmax. Blood glucose, insulin, HOMA-IR, and maximum running speed were assessed, and gene expression in bone tissue was measured using qRT-PCR. Data were analyzed using one-way ANOVA with Tukey post hoc testing (p < 0.05). Results Diabetic mice exhibited significant increases in glucose, insulin, and HOMA-IR, along with marked reductions in pluripotency gene expression, particularly at ZT3. Aerobic exercise significantly improved metabolic parameters and partially restored gene expression, with the greatest enhancement observed at ZT15. SOX2 and REX1 showed the most robust recovery under evening training conditions. Conclusion The findings indicate that circadian timing modulates the beneficial effects of aerobic exercise on pluripotency gene expression in diabetic bone tissue. Evening exercise (ZT15) exerts superior restorative effects, suggesting that chronobiology aligned training may serve as an effective strategy for improving bone regenerative potential in diabetes.